Wear Behavior of Tantalum Coated 316L Stainless Steel by DC Magnetron Sputtering for Orthopedic Applications - Pathote D.; Jaiswal D.; Singh V.; Behera C.K.; Gautam R.K. (My University, 2025)
In this study, the wear behavior of Ta-coated 316L Stainless steel (coating thickness of 1.504 μm, 3.809 μm, and 6.083 μm) by DC Magnetron Sputtering under the simulated body fluid (SBF) condition was optimized for the orthopedic applications. Stainless steel type 316L is the most widely chosen metallic material for artificial joints. However, the use of the metal is constrained, primarily for metal-on-metal, by the initiation of wear debris and metal ions. Coating of Tantalum can reduce the wear rate of these metal alloys. The Pin-on-disc biotribometer, manufactured by Ducom (TR-701), is used to evaluate tribological properties such as friction coefficient behavior and wear rate. This evaluation is being carried out in accordance with two ASTM standards - ASTM G133-95 and ASTM G99-95a. The bare 316L stainless steel has the highest wear rate of 42.97 mm3/Nm, while Ta-coated surfaces for 15, 30, and 60 min. have the wear rate of 11.25 mm3/Nm, 8.75 mm3/Nm, and 6.25 mm3/Nm, respectively. Based on wear study results, the wear rate was very low for Ta-coated (6.083μm) SS316L against bare. In order to characterize the morphology of the surface of worn bare and Ta-coated 316L SS, Optical Microscopy (OM), Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDAX), and Atomic Force Microscopy (AFM) were used. This study aims to show the performance of tantalum-coated stainless steel type 316L as an effective biomaterial with low wear behavior to apply for an implant. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.